2019
DOI: 10.3390/ijgi8060281
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Dynamic Time Warping for Grid-Based Travel-Demand-Pattern Clustering: Case Study of Beijing Bicycle-Sharing System

Abstract: Many kinds of spatial–temporal data collected by transportation systems, such as user order systems or automated fare-collection (AFC) systems, can be discretized and converted into time-series data. With the technique of time-series data mining, certain travel-demand patterns of different areas in the city can be detected. This study proposes a data-mining model for understanding the patterns and regularities of human activities in urban areas from spatiotemporal datasets. This model uses a grid-based method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…The demand near the residential areas is large in the morning peak period, and the demand near the commercial and industrial land is large in the evening peak period, and there is a significant difference between working days and non-working days. It is found that the demand hot spots in the morning peak period are mainly in the residential areas and the surrounding transportation hubs, and in the evening peak period, they are concentrated in the commercial and industrial land areas, which also corroborates the research of Refs [6,7,12]. In addition, we also found that during COVID-19, the link between the rail transit hubs and the shared bicycles was stronger than that between the buses and shared bicycles, which was also consistent with the findings of Ref [37].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The demand near the residential areas is large in the morning peak period, and the demand near the commercial and industrial land is large in the evening peak period, and there is a significant difference between working days and non-working days. It is found that the demand hot spots in the morning peak period are mainly in the residential areas and the surrounding transportation hubs, and in the evening peak period, they are concentrated in the commercial and industrial land areas, which also corroborates the research of Refs [6,7,12]. In addition, we also found that during COVID-19, the link between the rail transit hubs and the shared bicycles was stronger than that between the buses and shared bicycles, which was also consistent with the findings of Ref [37].…”
Section: Discussionsupporting
confidence: 84%
“…Shared cycling has a high degree of time regularity, which is significantly different during holidays and working days [5], and there are obvious tidal characteristics near the subway station in residential areas [6]. Gao et al [7] built a shared bicycle space model by combining land use information to analyze the distribution characteristics of strong source and sink points of the Beijing Mobike system and found that the distribution pattern of strong source and sink points has an obvious spatial-temporal heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al [11] proposed a data-mining model for exploring the regularities and patterns of human activities from complex spatiotemporal datasets. The model applies to a raster format of geospatial time-series data.…”
mentioning
confidence: 99%